1992
DOI: 10.1021/j100192a051
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations in the reaction rate of nitric oxide reduction by ammonia over polycrystalline platinum foil catalysts

Abstract: Self-sustained oscillations were obtained in the NO + NH3 reaction a t atmospheric pressure with reactant partial pressures of 133-600 Pa (1-4.5 Torr), in the temperature range of 603-673 K. The effects of reaction parameters, temperature, partial pressure, and reactant gas velocity were studied. The onset temperature of the oscillations (603 K) was slightly dependent on the partial pressure of nitric oxide in the feed gas. Near this temperature the oscillations were uncontrolled (chaotic), while increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 7 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…It was concluded that secondary reactions involving NO and NH 3 are the main cause for the occurrence of loss reactions in ammonia burners, yielding the undesired N 2 O and N 2 products. The mechanism and kinetics of the NO reduction by NH 3 in the absence of O 2 have been investigated over platinum catalysts of different nature, including single crystals (Pt(1 0 0) [4,5] or stepped Pt 12(1 1 l) Â (l 1 1) [6]), polycrystalline Pt wire [7,8] and foils [9][10][11], as well as supported Pt catalysts [12][13][14], at different molar feed NH 3 /NO ratios (1)(2)(3)(4)(5)(6)(7)(8)(9), pressures (0.1-1000 Pa), and temperatures (473-873 K), using batch and flow reactors, as well as surface science techniques in ultra-high vacuum (UHV). N 2 (mainly) and N 2 O were found as the reaction products, with a typical increase in the N 2 /N 2 O ratio upon increasing the temperature and/or the feed NH 3 concentration [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that secondary reactions involving NO and NH 3 are the main cause for the occurrence of loss reactions in ammonia burners, yielding the undesired N 2 O and N 2 products. The mechanism and kinetics of the NO reduction by NH 3 in the absence of O 2 have been investigated over platinum catalysts of different nature, including single crystals (Pt(1 0 0) [4,5] or stepped Pt 12(1 1 l) Â (l 1 1) [6]), polycrystalline Pt wire [7,8] and foils [9][10][11], as well as supported Pt catalysts [12][13][14], at different molar feed NH 3 /NO ratios (1)(2)(3)(4)(5)(6)(7)(8)(9), pressures (0.1-1000 Pa), and temperatures (473-873 K), using batch and flow reactors, as well as surface science techniques in ultra-high vacuum (UHV). N 2 (mainly) and N 2 O were found as the reaction products, with a typical increase in the N 2 /N 2 O ratio upon increasing the temperature and/or the feed NH 3 concentration [7].…”
Section: Introductionmentioning
confidence: 99%
“…In general, due to the correlations related to spatial constraints, these probabilities are not reduced to the average coverages of a site. To articulate the difference in the treatments of the reaction kinetics on single sites or pairs of sites and in an adsorbed overlayer, it is of interest to mention that under certain conditions the reaction (1) exhibits kinetic oscillations on polycrystalline Pt [14][15][16]. Such oscillations are usually associated with non-linear dependence of the rates of reaction steps on adsorbate coverages.…”
Section: Resultsmentioning
confidence: 99%
“…93,173,202,203] suggesting the subsequent dehydrogenation of ammonia: -NH3  -NH2  -NH  -N, until the formation of Nads species, which interact with Oads to produce NO [e.g. [204][205][206][207] and NO2 [30], while the formation of N2 occurs by interaction of two Nads species [138] over noble metals. Recently, Cui et al [138] proposed a synergistic catalytic effect between RuO2 and CuO during ammonia oxidation suggesting that coordinatively unsaturated Ru atoms (cus), present in RuO2 can easily adsorb and activated NH3 molecules and oxygen atoms.…”
Section: The Mechanisms Of Nh3-scomentioning
confidence: 99%
“…Therefore, a significant population of NH3-x species on their surface could be expected [30]. Such species were reported to react with NO to form N2 and/or N2O [205,206,208,209]. Experiments of Burch and Southward [37] emphasized that under rich conditions (NH3:O2 = 1:1), CuO was partially reduced by ammonia to produce a reservoir of NH3-x species.…”
Section: The Mechanisms Of Nh3-scomentioning
confidence: 99%